Prognostic Model of Colorectal Cancer Constructed by Eight Immune-Related Genes - Wen, Shuting; He, Long; Zhong, Zhuotai; Mi, Hong; Liu, Fengbin (Frontiers in Molecular Biosciences, 2020)
Background:Colorectal cancer(CRC) is a common malignant tumor of the digestive tract with a high mortality rate.Growing evidence demonstrates that immune-related genes play prominent role in the occurrence and development of CRC.The aim of this study was to investigate the prognostic value of immune-related genes in CRC. Methods:Gene expression profiles and clinical data of 568 CRC and 44 non-tumorous tissues were obtained from The Cancer Genome Atlas (TCGA) database.First,We performed differentially expressed gene(DEG) analysis and univariate Cox regression analysis,in order to determine DEGs associated with overall survival.Gene Ontology(GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were subsequently performed for prognostic immune-related genes.Furthermore,multivariate Cox regression analysis was performed to establish the immune prognostic model and identify the independent prognostic factors of CRC.Finally,we also analyzed the correlation among immune-related genes,clinical traits and immune cells infiltration. Results:In total, 3702 DEGs were obtained,and 338 prognostic immune-related genes were identified.Among them,45 genes were significantly correlated with the prognosis of CRC patients.TF-mediated network was set up to explore its internal mechanism.GO and KEGG analyses further illustrated that these genes were enriched in immune and inflammatory related pathways.Then,a prognostic prediction model composed of eight immune-related genes(SLC10A2,UTS2,FGF2,UCN,IL1RL2, ESM1,ADIPOQ,VIP) was constructed.The AUC of the ROC curve for 1-year,3-year,5-year and 10-year OS were 0.751,0.707,0.680 and 0.729,respectively. Survival analysis suggested that overall survival (OS) of the high-risk group was significantly poorer than low-risk group,validating the accuracy of the model.Correlation analysis indicated immune cells infiltration were positive related to the model. Conclusions:This study screened out prognosis-related immune genes and developed a prognostic prediction model of CRC.These findings may help provide potential novel prognostic biomarkers and therapeutic targets for CRC.At the same time,the understanding of CRC immune microenvironment status was deepen.